Strategic plan to enforce changes in speeding behaviour Australian vs. Indian perspective - Ebrahim, Zuhair; Nikraz, Hamid (International Road Federation - India Chapter, 2011)
The most important pillar of UN road safety plan for the next ten years is enforcing a change in risky behaviour towards safer road use. One persistent concern of this man made behavioural calamity is speeding. Speeding is not only a concern for developed countries i.e. USA, Europe and Australia, but continuing to be of alarming concern for many Asian countries, India, Pakistan, many countries in Africa and the Middle East. This paper aim will focus on highlighting twenty years of Australian research, intervention and implementation in tackling speeding. It is certain, that some of the reflection of the examples mentioned will create additional materials to the Indian action plan chapter into road user behavioural modification. Speed limit compliance is one important part of the Australian road safety culture. Liaising with communities, authorities have manages to make many positive decisions on adopting low speed limits such as the successful examples of school zones and other recent areas mentioned in this paper. In addition to the laborious public education and extensive advertising campaigns, Australian authorities converted road rules into tools to indirectly change road user’s behaviour. This conversion had the potential to reduce road accidents and fatalities to a tangible level despite the increase of vehicles registrations. This brought confidence between authorities and the majority of drivers that complied with the speed limit which lead at the end to positive results. The strategy of Australian policymakers focused on specific and general deterrence in curbing speeding behaviour, using the most sophisticated fixed and mobile enforcement cameras.The mission of strategy is (anywhere-anytime) and most importantly depriving offenders from positive consequences if they thought of speeding. The strategic deterrence was to make drivers slow down and examples will show the trend of speed compliance. Authorities concentrated on two types of drivers those who drove with excessive- level speeding and those with low-level speed including repeat offenders. Enforcing posted speed limit is an important part of the Australian strategy plan and India may need to examine further how Australia enforced different limits in urban and rural areas. Australian authorities have shown that it is one thing to have the posted speed limits on the roads, but what matters is how to plan to enforce them. Such as how Australian authorities started with fixed cameras and enlarged the force to include covert mobile speed cameras. In other word a worthy spending may be of benefit and still able to direct the revenue from speeding fines towards the remedy of unsafe locations e.g. black spots etc. India may need to review road rules regarding heavy vehicles, speed limit and or rearrange them or make new laws that become part of the road safety mission which firstly requires to ensure the sustainability of the safe road use and secondly to aim at creating slowly but surely, a culture that can become the bone of the strategy of such vital behaviour. For the Indian chapter view point, the sustainability must involve an active interventions aiming to reduce speeds through engineering measures and law enforcement that are discussed in details in this paper. It is also vital to remember that speed cameras are only one of the tools used in enforcing speed limit compliance, other behavioural and communication tools need to be added on board to make a comprehensive road safety strategy.